Relationship Between the Ergonomic State of the Classroom Measured in Energy Units and the Well-Being of Students Observed by Non-Invasive Instrumentation - Cordova-Gonzalez, F; Palominos-Villavicencio, F; Canete-Arratia, L; Diaz-Munoz, H (Elsevier B.V., 2015)
This work aims to measure the ergonomic level of a classroom by means of the quantification of two readily measurable variables. The central hypothesis is that the greater the ergonomic level of the classroom, the higher the well-being of the students and, consequently, the less of total environmental adjustments that must be done to achieve a comfortable situation. Previous research put forward that when human beings are faced with nonpleasing environments, immediately emerges a state of restlessness, which is behaviorally manifested by postural changes and surrounding observation assessing both the sources of discomfort and the potential resources to avoid them. This fact is mainly attested by the movements of the head, the part of the body that concentrates all the sensory system, and the rest of the body. Regarding that the well-being experienced by a student in a specific learning environment is reflected in the body of the individual, we choose to measure these movements as a proxy variable of the ergonomic level of the classroom. A second variable can be measured during the first few minutes of the class by recording the distance displacement of objects and the modification of other aspects of the classroom made by the students to get a better condition to be in it. We choose the net amount of energy required to do these changes as another proxy variable to estimate the ergonomics of the classroom. This second variable is measured once the students are free to make adjustments in the classroom quantifying the energy used for this purpose. These observations are plotted on a Cartesian plane revealing a clear correlation between energy and movements, confirming that both variables are quantitative indicators of the ergonomic state of the classroom, the main artificial ecosystem of learning. ©2015 Published by Elsevier B.V.